Proximate and Phytochemical Constituents of Ethanolic Extract of Seeds of Cola Acuminata and Cola Nitida - Osaro, Igwe Esther; Chinedu, Imo; Ojochenemi E, Yakubu (Darul Yasin Al Sys, 2024)
This study evaluated the proximate and phytochemical constituents of ethanolic seeds extracts of Cola nitida and Cola acuminata. The seeds of C. acuminata and C. nitida were purchased and air-dried at room temperature. The dried seeds were pulverized to ground sample. The sample was weighed and used for the proximate and phytochemical analysis. The qualitative phytochemical screening revealed the presence of secondary metabolites: alkaloid, flavonoids, tannins, phenols, Cardiac glycoside, terpenes (tri), steroids and saponins, but the absence of anthraquinones. The seed of C. nitida was higher in alkaloids, saponins, phenols, tannins, steroids, triterpenes and C-glycosides than the seed of C. acuminata, while the seed of C. acuminata was higher in flavonoids and carbohydrates than the seed of C. nitida. There was no statistical significant difference (p>0.05) between the levels of alkaloids, saponins, phenols and tannins in seed of C. nitida and seed of C. acuminata. The difference between the levels of flavonoids, carbohydrates, steroids, triterpenes and C-glycosides in seed of C. nitida and seed of C. acuminata was statistically significant (p<0.05). The seed of C. nitida was higher in moisture, ash, lipid and crude protein than the seed of C. acuminata, while the seed of C. acuminata was higher in crude fibre and carbohydrate than the seed of C. nitida. There was no statistically significant difference (p>0.05) between the levels of moisture, ash, lipid, crude fibre and crude protein in seed of C. nitida and seed of C. acuminata. The difference between the level of carbohydrate in seed of C. nitida and seed of C. acuminata was statistically significant (p<0.05). The result shows that seeds of C. acuminata and C. nitida possess an appreciable level of phytochemicals. It could be a good raw material for the production of some medicinal drugs and can be used in folk medicine for the treatment of some diseases.